Features and outcome of surgical management of spinal tumors in a cohort of nigerian patients (2014)
OBJECTIVE: There is a dearth of information on operated cases of spinal tumors in patients in sub-Saharan Africa. The objective of this study was to evaluate the histologic pattern, anatomic distribution, and extent and outcome of surgery of Nigerian patients with spinal tumors. METHODS: This retrospective study comprised a cohort of Nigerians who underwent surgery for spinal tumors. Data obtained included patient demographics, duration of symptoms, anatomic location, imaging findings, Frankel grading before and after surgery, and type and outcome of surgery. Univariate analysis was performed, and results were compared with results from other parts of the world. RESULTS: There were 59 patients (male-to-female ratio 1:1.1) with a bimodal age distribution. The highest (20.34%) incidence was seen in the 20e29 age group. More than half (58.06%) of the patients presented with a duration of symptoms of at least 6 months (duration of symptoms was >12 months in 35.48%). Motor deficit was present in 97.73% of patients at presentation. Functional grading was Frankel A in 38.10% of patients, Frankel C in 26.19%, Frankel B in 16.67%, Frankel D in 16.67%, and Frankel E in 2.38%. The tumors were mostly in the thoracic region (65.45%), and 58% were extradural in location. Gross total tumor excision was performed in 50.88% of the cases, and subtotal resection was performed in 24.56%. Spinal stabilization was performed in 17.86% with spinous process wiring and vertical strut being the most common method of stabilization (80%) among this group. Metastasis was the most common histologic tumor type (23.21%). Meningioma accounted for 12.50% of tumors, and ependymoma, astrocytoma, and hemangioma each accounted for 7.14%. The most common source of metastasis was the prostate (38.46%). Postoperatively, 45% of patients improved neurologically, 52.5% remained the same, and 2.5% deteriorated. There was no perioperative mortality. CONCLUSIONS: Metastasis was the most common histologic type of spinal tumor in this study, and the most common location was extradural. The outcome was satisfactory in most cases with neurologic function remaining the same or improving after surgery in most patients.